Prediction of explosive properties of newly synthesized amino nitroguanidine-based energetic complexes via density functional theory - Roohzadeh, Rouhallah; Mahdavi, Mohammad (Journal of molecular modeling, 2020)
Density functional theory calculations were performed to explore four octahedral energetic complexes including [CoCl 2 (ANQ) 2 ], [Co (ANQ) 2 (H2O) 2 ] 2+ , [CuCl 2 (ANQ) 2 ], and [Cu(NO3) 2 (ANQ) 2 ], (ANQ = amino nitroguanidine). In this work, an attempt has been made to present useful structural data in order to investigate and predict the explosive properties of these complexes. In this regard, interaction energy (IE), natural bond orbital (NBO), atoms in a molecule (AIM) as well as the three-dimensional Hirshfeld surface analysis and the two-dimensional fingerprint plots, charge transfers, HUMO-LUMO gap, oxygen balance (%OB) amounts, and molecular electrostatic potential (MEP) maps were utilized to assign intermolecular interactions, bond lengths, the nature of metal-ligand bonds, and energies in subject compounds. The results reveal that among the five applied levels of theory, interaction energies obtaining from M06-2X/Def2TZVP were in excellent compliance with the experiments. Additionally, the N⋯O interaction, oxygen balance, density, and HOMO–LUMO gap were the most contributing factors in assigning sensitivity and detonation properties. In general, the sensitivity and detonation properties are increased in the following order: ANQ < complex1 < complex3 < complex2 < complex4. Graphical abstract